2011
DOI: 10.1124/dmd.111.041335
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Expression and Activity of Carboxylesterases 1 and 2 from the Beagle Dog, Cynomolgus Monkey, and Human

Abstract: ABSTRACT:The carboxylesterases (CESs) are a family of serine hydrolases that hydrolyze compounds containing an ester, amide, or thioester. In humans, two dominant forms, CES1 and CES2, are highly expressed in organs of first-pass metabolism and play an important role in xenobiotic metabolism. The current study was conducted to better understand species-related differences in substrate selectivity and tissue expression of these enzymes. To elucidate potential similarities and differences among these enzymes, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 16 publications
(36 reference statements)
3
57
0
Order By: Relevance
“…The anti-human CES1 antibody used in the present study was reported to be CES1-specific, without cross-reactivity with CES2 proteins, by probing against cynomolgus monkey, dog, and human CES1 and CES2 enzymes (Williams et al, 2011). As previously reported (Satoh and Hosokawa, 2010;Williams et al, 2011), CES1 proteins were highly expressed in the liver in the three species, and were significantly expressed in monkey intestine and kidney, dog kidney, lung, and plasma, and human lung as a single band with a molecular mass approximately at 60 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-human CES1 antibody used in the present study was reported to be CES1-specific, without cross-reactivity with CES2 proteins, by probing against cynomolgus monkey, dog, and human CES1 and CES2 enzymes (Williams et al, 2011). As previously reported (Satoh and Hosokawa, 2010;Williams et al, 2011), CES1 proteins were highly expressed in the liver in the three species, and were significantly expressed in monkey intestine and kidney, dog kidney, lung, and plasma, and human lung as a single band with a molecular mass approximately at 60 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition potencies of DFP and eserine to prasugrel hydrolysis by dog AADAC appeared to be slightly lower than those by human AADAC. It was reported that the IC 50 value of loperamide was 0.562 mM for purified human CES2, whereas that for purified dog CES2 was 93.6 mM (Williams et al, 2011). Thus, the differences in the inhibitory potencies of DFP and eserine are due to species differences.…”
Section: Discussionmentioning
confidence: 98%
“…4A). However, the 4-NPV assay, which measures CES activity (Williams et al, 2011), showed that total CES activity was only 2-fold lower in the skin than in the liver (Fig. 4B), confirming the potential for human skin to contribute to the metabolism of ester compounds when applied transdermally .…”
Section: Downloaded Frommentioning
confidence: 92%
“…These structural differences result in different substrate specificity. CES1 tends to hydrolyze molecules with a small alcohol moiety more efficiently, whereas CES2 is more efficient at metabolizing molecules with a larger alcohol moiety and more lipophilic molecules (Brzezinski et al, 1994;Williams et al, 2011). These differences in the substrate specificity of CES1 and CES2 could lead to differences in predicting skin absorption or metabolism.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation